Bis(4,4′-sulfanediyldipyridinium) tetrachloridonickelate(II) dichloride - Werner, Julia (International Union of Crystallography, 2012)
In the title compound, (C(10)H(10)N(2)S)(2)[NiCl(4)]Cl(2), the Ni(2+) cation is tetrahedrally coordinated by four chloride anions. Two 4,4′-sulfanediyldipyridinium cations and two non-coordinating chloride anions are connected via N—H⋯Cl hydrogen-bonding interactions into 20-membered rings, in the middle of which are situated the [NiCl(4)](2−) complex anions. These rings are stacked in the b-axis direction. The Ni(2+) cation is located on a twofold rotation axis, whereas the chloride anions and the 4,4′-sulfanediyldipyridinium cations occupy general positions.